Propuesta de un sistema de gestión de calidad basado en la norma ISO 9001:2015 para mejorar la calidad del servicio de distribución secundaria de agua potable en el equipo operación y mantenimiento de redes San Juan de Lurigancho - Sedapal - . Deza Guzmán, Diana Corina (2023)
The general objective of this research is to improve the quality of the secondary distribution service of drinking water in the operation and maintenance team of the San Juan de Lurigancho (EOMR-SJL) - Sedapal networks with the proposal of implementation of a quality management system (QMS) based on the ISO 9001: 2015 standard. In the initial diagnosis of Sedapal's "secondary distribution of drinking water" process, it was found that user satisfaction with respect to the quality of the water received was 59.6% in 2018. In addition, in the same year the capacity was evaluated. of the process and it turned out that it was not potentially capable of meeting the accepted specifications of the service. Subsequently, it was verified that compliance with the requirements of ISO 9001: 2015 in the EOMR-SJL reached 14.80%. That is why the documented information and the quality management system implementation plan were designed based on the requirements of the standard for its implementation and maintenance. By applying the QMS, the process will be better planned, organized and standardized, therefore, there will be better control of the parameters that regulate the distribution of water and non-conforming outputs will be reduced, this was evidenced in the year 2020 when implementing in a 68.37 % the SGC based on the ISO 9001:2015 Standard in the EOMR-SJL regarding the secondary distribution process of drinking water, where the following results were obtained: user satisfaction regarding the quality of the water received increased by 11.3 % since it reached a value of 70.9% in the year 2020, unlike the satisfaction result of the year 2018, which obtained a value of 59.6%. In addition, by implementing the QMS, the product quality specifications are met, because with respect to the residual free chlorine parameter, a Cp of 1.75 was obtained, Cpk of 1.20 and DPMO (expected in the long term) of 162 ppm and with respect to the turbidity parameter, a Cp of 1.60, Cpk of 1.22 and DPMO (expected in the long term) of 114 ppm were obtained; which reveals that the implemented process is capable of meeting the product specifications